Sovereign Risk and Secondary Markets - Broner, Fernando; Martin, Alberto; Ventura, Jaume (American Economic Review, 2010)
Conventional wisdom says that, in the absence of default penalties, sovereign risk destroys all foreign asset trade. We show that this conventional wisdom rests on one implicit assumption: that assets cannot be retraded in secondary markets. Without this assumption, foreign asset trade is possible even in the absence of default penalties. This result suggests a broader perspective regarding the origins of sovereign risk and its remedies. Sovereign risk affects foreign asset trade only if default penalties are insufficient and secondary markets work imperfectly. To reduce its effects, one can either increase default penalties or improve the working of secondary markets. (JEL F34, G12, G15)